Production of Oleic Acid Based Wax Ester Using Acidic Homogeneous Catalysts - Naowara Al-Arafi; Jumat Salimon (E-Journal of Chemistry)
Four homogeneous acidic catalysts were tested for their ability to catalyze the esterification reaction of oleic acid and oleyl alcohol to produce oleyl oleate, a wax ester. Sulfuric acid showed relatively higher specific activity. Various reaction parameters were optimised to obtain high percentage yield of oleyl oleate. The optimum condition to produce oeyl oleate was reaction time; 5 h, temperture; 90°C, amount of sulforic acid 0.15 g and molar ratio of oleyl alcohol to oleic acid; 1:1. Percentage yield of wax ester obtained at these optimum reaction conditions was 93.88. Disappearance of carboxylic acid (C=O) peak has confirmed by FTIR with appearance of ester (C=O) peak at 1739 cm−1. 1H NMR spectra analyses confirmed the result of oleyl oleate with appearance of ester (-CH2OCOR) at 4.02 ppm and also the 13C-NMR confirmed the result with appearance of ester (C=O) peak at 173.2 ppm. The low-temperture behavior of compound synthesized was determined through its pour point (PP), viscosity index (VI) and flash point (FP) values. The results showed that oleyl oleate exhibited the most favorable low-temperture performance of PP, VI and FP with −31°C, 197.5 and 320°C respectively. This is due to increase of the molacular weight thus improve the low temperture property significantly.